“A doença como o vento” : representações sociais de diabéticos da comunidade São Gonçalo Beira Rio – Cuiabá/MT - Monçale, Aline Grasielli (2012)
This study has as central question the perception of social representations about diabetes mellitus in the vision of its own diseased; for this are introduced the conceptions of health and disease through non-diabetic local informants to give meaning and sense to the question of the main actors, the three social agents with diabetes. The place of the ethnographic work was the Riverside Community São Gonçalo in Cuiabá / MT, being, therefore the "rags-to-bottom" that contextualizes the lifestyles and choices; the use of concepts from Pierre Bourdieu's theory guided the research and provided fertile ground for the extrapolations more subtle and deep. The research is justified by the evolution of the importance of the issue of chronic degenerative diseases, among them the figuration of diabetes mellitus as a public health problem, added to the fact that there are few qualitative studies, especially in the place chosen, on this issue. The way the social actors live the disease process is mediated through the historical and cultural habitus, and they’re submitted to a constant reinterpretation with every each new contact, whether through personal experiences and other people ones, information and other biomedical knowledge. Through the symbolic dimension, the diabetics sometimes classify diabetes as a disease only when it unable them to perform their social roles, sometimes as worrying when it shakes the "silence of the organs." Reveal this universe, its codes and values provide important elements in order to think and health care.